Prevalence and prognostic value of baseline sarcopenia in hematologic malignancies: a systematic review - Zeng, Xiaofeng; Zhang, Liying; Zhang, Yu; Jia, Shuli; Lin, Taiping; Zhao, Xuman; Huang, Xiaoli (Frontiers in Oncology, 2023)
Background: The correlation between sarcopenia and hematological malignancy prognosis is still controversial. Design: A systematic review and meta-analysis. Objectives: To explore sarcopenia's prevalence and prognostic value in hematologic malignancies. Data Sources and Methods: We searched Embase, MEDLINE, and Cochrane Library through Ovid SP using an appropriate search strategy on August 28, 2022, and updated the search results on January 9, 2023. Study quality was assessed using the Newcastle-Ottawa scale. The pooled prevalence of sarcopenia was calculated with 95% confidence interval (CI). Relationships between sarcopenia and prognostic value were expressed as hazard ratio (HR) and 95% CI. HR means the probability of something undesirable, i.e., death or disease progression. Results: The search identified more than 3992 studies, and 21 (3354 patients, median or mean age ranging from 36 to 78 years) were finally included. The risk of bias in the studies was low to medium. All included studies were diagnosed based on low muscle mass (LMM). Muscle mass was assessed mainly through imaging technologies, and different cut-offs were applied to determine LMM. The prevalence of sarcopenia was 44.5%, which could be fluctuated by age. Subgroup analysis showed that older people hold a higher sarcopenic rate than the nonelderly group. Sarcopenia resulted in an inferior prognosis [overall survival (OS):: HR 1.821, 95% CI 1.415-2.343; progression-free survival (PFS):: HR 1.703, 95% CI 1.128-2.571). Conclusion: Sarcopenia has a prevalence of over 30% in malignant hematologic patients and is associated with a poorer prognosis. Future studies with a standardized sarcopenia diagnostic criterion were needed to investigate sarcopenia's prevalence and prognostic effects in hematologic malignancies.